Ethnopedagogy as an Integrative Framework for Developing Scientific Ethics and Character Integrity in Elementary Education: A Systematic Literature Review - Juwanti Juwanti; Oktaviani Adhi Suciptaningsih; Aynin Mashfufah; Ade Eka Anggraini (Papanda Publisher, 2026)
Elementary education requires innovative approaches that integrate character development with cultural values to address Society 5.0 challenges. This systematic literature review synthesizes empirical evidence on ethnopedagogy's contribution to developing scientific ethics and character integrity among elementary school students. Following PRISMA 2020 guidelines, we systematically searched seven databases (Scopus, ERIC, SAGE, DOAJ, Google Scholar, Garuda, Neliti) for peer-reviewed articles published between 2022-2025. Initial screening identified 280 articles, reduced to 30 high-quality studies through systematic selection using JBI and CASP quality appraisal tools. Thematic analysis synthesized findings across moral values, social competencies, academic integrity, pedagogical approaches, and community engagement dimensions. Ethnopedagogical approaches consistently cultivated moral values through culturally embedded learning experiences, enhanced social competencies via collaborative cultural practices, and developed academic integrity through rule-governed traditional activities. Discovery learning models based on local wisdom significantly increased students' curiosity, responsibility, and cultural understanding. Community involvement emerged as essential infrastructure, with active partnerships strengthening character development outcomes. However, urban-rural disparities and implementation variability indicate context-specific adaptation needs. Findings support ethnopedagogy as a comprehensive framework integrating affective dispositions and cognitive-behavioral competencies. The four-stage integrative model—cultural exploration, reflective internalization, contextual application, and character transformation—provides theoretically grounded guidance for culturally responsive character education. Future research should address methodological limitations through experimental designs, longitudinal investigations, and cross-cultural comparative studies to strengthen evidence-based implementation.